Upaya Meningkatkan Hasil Belajar Siswa Dalam Mata Pelajaran Sejarah Kebudayaan Islam Dengan Menggunakan Model Pembelajaran The Learning Cell Di Kelas 8 MTs Negeri 1 Palembang - Hasnarita Hasnarita (JURNAL PENDIDIKAN DAN ILMU SOSIAL (JUPENDIS), 2023)
The problem formulation in this classroom action research is "Can the application of the quiz learning model improve learning outcomes in SKI subjects for class VIII students at MTs Negeri 1 Palembang in the 2018/2019 academic year?" Research results: the application of the quiz learning model can improve student learning outcomes in Islamic Religious Education subjects in class VIII MTs Negeri 1 Palembang for the 2018/2019 academic year. In the pre-cycle (initial condition) the average value of student learning outcomes was 49.33 with the number of students who completed it being 7 people (23%). In cycle I the average value of student learning outcomes was 68.77 with the number of students who completed it being 15 people (50%). In cycle II the average value of student learning outcomes was 86.17 with the number of students who completed it being 27 people (90%). So, it can be concluded that this research can be categorized as successful.